1998
DOI: 10.1002/(sici)1521-4141(199802)28:02<610::aid-immu610>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Gene transfer with IL-4 and IL-13 improves survival in lethal endotoxemia in the mouse and ameliorates peritoneal macrophages immune competence

Abstract: Systemic anti-cytokine therapies have been unsuccessful in preventing mortality from gram-negative bacteremia in humans partly because of the failure to neutralize pro-inflammatory cytokines at sites of exaggerated production. In an attempt to deliver anti-inflammatory cytokines to organs directly, gene transfer was employed. Thirty-six BALB/c mice were injected intraperitoneally with cationic liposomes containing plasmids encoding the human interleukin-4 (hIL-4) or IL-13 gene. Both, hIL-4 and hIL-13 mRNA were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
26
0

Year Published

1999
1999
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(27 citation statements)
references
References 22 publications
1
26
0
Order By: Relevance
“…Therefore, we conclude that the IL-13-reduced NO production is regulated by at least two mechanisms, the up-regulated arginase activity and the down-regulated iNOS expression. These results also suggest that the induced arginase, by inhibiting NO production from activated macrophages, may contribute at least in part to the observed anti-inflammatory effect of IL-13 in vivo (42). It is worth noting that L-norvaline specifically inhibits arginase activity at the enzyme kinetic level (15,26), and it does not affect iNOS expression, as shown in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we conclude that the IL-13-reduced NO production is regulated by at least two mechanisms, the up-regulated arginase activity and the down-regulated iNOS expression. These results also suggest that the induced arginase, by inhibiting NO production from activated macrophages, may contribute at least in part to the observed anti-inflammatory effect of IL-13 in vivo (42). It is worth noting that L-norvaline specifically inhibits arginase activity at the enzyme kinetic level (15,26), and it does not affect iNOS expression, as shown in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…This concept is supported by much evidence derived from studies in animal and in human systems in which the systemic injection of LPS or live bacteria or the presence of bacterial infection is associated with the sustained production of proinflammatory cytokines. Various studies in animal models have demonstrated the protective effect of anti-cytokine maneuvers, including the administration or induced expression of the Th2 cytokines IL-10 (17-19) and IL-4 (20). In addition, the antiinflammatory cytokine IL-13 has been found to provide protection from LPS-induced endotoxemia in a manner that is similar to but distinct from that of IL-10 (23).…”
Section: Discussionmentioning
confidence: 99%
“…IL-10 can act as a potent modulator of cytokine production and lethality in LPS-induced pathology (17)(18)(19). Gene transfer with IL-4 improves survival in lethal endotoxemia (20), and selective, compartmentalized blockade of TNF-␣ overproduction by IL-4 enhances pulmonary clearance of Pseudomonas aeruginosa in mice (21). We have recently shown that rIL-4 may protect animals from death in a toxic shock model with the bacterium, correlating with decreased levels of circulating TNF-␣ soon after challenge (22).…”
Section: Il-9 Protects Mice From Gram-negative Bacterial Shock: Supprmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 Several groups have demonstrated that liposome and plasmid-mediated expression of either IL-10, soluble TNF receptors, COX-2, IL-4 or IL-11 could reduce the inflammatory consequences of endotoxin shock or caerulein-induced pancreatitis. [15][16][17][18] However, these therapies were generally administered hours or days before the induction of experimental inflammation, and the resulting inflammatory response to the administered liposomes and plasmid DNA may have induced tolerance in these animals and contributed to the improved morbidity and mortality. The present study examined whether the inflammatory response to administered liposomes and plasmid DNA could affect the outcome during experimental inflammation.…”
Section: Figure 4 Markers Of the Systemic Acute Inflammatory Responsementioning
confidence: 99%